Bending resistance and cyclic fatigue of a new heat‐treated reciprocating instrument. Issue 6 (11th June 2016) - Silva, Emmanuel João Nogueira Leal; Rodrigues, Cristiane; Vieira, Victor Talarico Leal; Belladonna, Felipe Gonçalves; De‐Deus, Gustavo; Lopes, Hélio Pereira
Summary: The current study aimed to evaluate the bending resistance and the cyclic fatigue life of a new heat‐treated reciprocating instrument (ProDesign R). Untreated ProDesign R, Reciproc R25, and WaveOne Primary instruments were used as reference instruments for comparison. The bending resistance was performed in ten instruments of each system by using a universal testing machine and a proper apparatus. The cyclic fatigue resistance was tested measuring the number of cycles to failure in an artificial stainless steel canal. Scanning electron microscopy analysis was performed to determine the mode of fracture and possible deformations at the helical shaft. Statistical analysis was performed by using parametric methods; one‐way analysis of variance plus post hoc pair‐wise Tukey test for multiple comparisons (p < 0.05). Untreated ProDesign R presented significantly higher bending resistance than the other tested systems (p < 0.05). No differences were observed between ProDesign R and Reciproc files regarding the bending resistance (p > 0.05). Moreover, ProDesign R revealed a significantly longer cyclic fatigue life (p < 0.05). In contrast, Untreated ProDesign R and WaveOne instruments presented significantly lower cyclic fatigue life than Reciproc (p < 0.05). The new heat‐treated reciprocating instrument ProDesign R have higher cyclic fatigue resistance than Untreated ProDesign R, Reciproc, and WaveOne instruments. ProDesign R and Reciproc were significantly more flexible than Untreated ProDesign R and WaveOne files. SCANNING 38:837–841, 2016. © 2016 Wiley Periodicals, Inc.